ARTSAKH: DISCOURSE STUDY OF THE CASE AGAINST DISCRIMINATION - Gasparyan, Seda; Hayrapetyan, Zara (Armenian Folia Anglistika, 2024)
The following article addresses the long-lasting conflict between Armenia and Azerbaijan the center of which is Artsakh. The case was taken to the International Court of Justice. We strive to analyze the case by studying the speech of each countries’ representative, i.e. Yeghishe Kirakosyan’s speech representing Armenia, and Elnur Mammadov’s speech representing Azerbaijan. Our goal in this article is to unveil some linguistic, extra-linguistic, and rhetorical properties present in their speeches. Linguisic means may be detrimental in affecting the judges’ decision, hence the intersection of legal discourse and linguistics creates a wider opportunity to reach a better outcome.
Keywords: Armenia’s speech; Azerbaijan’s speech; linguistic strategies and techniques; discourse analysis; rhetorical means; extra-linguistic features